Legal highs: what should we do about synthetic cannabis? - Barratt, Monica; Bright, Stephen (The Conversation, 2012)
Synthetic cannabis is a lab-made product that mimics the effects of cannabis to give users a high when smoked. It has been sold in Australia since 2011 under various brand names, with a range of chemical compositions. The product presents a unique challenge for drug policymakers. Despite 18 months of legislative action intended to ban synthetic cannabis, people in some states claim they can still walk into a sex store or tobacconist and purchase it. Clearly the legislative changes have not been totally effective.